Feed them to the lions: Conservation violence goes online. Issue 79 (February 2017) - Lunstrum, Elizabeth
Highlights: Web 2.0 applications enable the unleashing of conservation-related violence. The roster of actors behind conservation violence has expanded to include the public. Conservation-related cyber-violence authorizes lethal green militarization. Demands for violence against poachers call for their Agambian abandonment. This violence turns on a dialectic of abandoning the human & embracing the non-human. Abstract: Web 2.0 applications like Facebook and Twitter have enabled the development of online communities that have exposed and decried violence against animals including wildlife. One of the most active of these communities has organized around concern for the rhino in the face of escalating commercial poaching. On closer look, a deeply concerning relation between conservation and violence emerges through these platforms. Namely, community members routinely advocate extreme violence against poachers, ranging from shoot-on-sight policies to outright torture. Analyzing user comments on South African National Parks Facebook rhino poaching updates, I illustrate how Web 2.0 applications have become powerful tools of imagining and promoting conservation-related violence. These amount to an Agambian abandonment of poachers to a realm beyond human protection, which spins on a dehumanization of poachers and inverse invitation of rhinos into the national community. In short, the violence turns on a dialectic of abandonment and belonging, of abandoning the human and embracing the non-human. The case highlights both the expanding roster of actors behind conservation violence, as it includes facets of the public, and the growing spaces through which such violence unfolds, as it enters cyberspace. And while the contributions of these actors may seem relegated to online worlds, they come to matter. In particular, they authorize state militarized violence that results in the death of suspected poachers and in turn threatens long-term conservation efforts. More broadly, I illustrate how Web. 2.0 applications are productive of cyber-violence beyond hate and fascist groups as they expand to include conservation activism.